2002
DOI: 10.1200/jco.2002.08.128
|View full text |Cite
|
Sign up to set email alerts
|

Therapy-Related Myeloid Leukemias Are Observed in Patients With Chronic Lymphocytic Leukemia After Treatment With Fludarabine and Chlorambucil: Results of an Intergroup Study, Cancer and Leukemia Group B 9011

Abstract: Our findings raise the possibility that alkylator-purine analog combination therapy may increase the risk of therapy-related myeloid malignancies, which is of particular relevance with regard to ongoing trials using these combination therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
112
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 166 publications
(124 citation statements)
references
References 28 publications
6
112
1
5
Order By: Relevance
“…24,25 Despite potent myelosuppression, therapyrelated myeloid neoplasms secondary to fludarabine single-agent treatment is extremely rare, reported 0 in 174 (0%) and 1 in 188 (0.5%) in two studies conducted on chronic lymphocytic leukemia/small lymphocytic lymphoma patients who received fludarabine as initial therapy with a long-term followup. 26,27 However, the incidence of therapy-related myeloid neoplasms is significantly higher in the setting of fludarabine combination therapy. [13][14][15][16]26,28 It has been postulated that fludarabine inhibits DNA repair 29 and acts synergistically with DNA-damaging agents, such as cyclophosphomide.…”
Section: Therapy-related Myeloid Neoplasm Post Fcrmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Despite potent myelosuppression, therapyrelated myeloid neoplasms secondary to fludarabine single-agent treatment is extremely rare, reported 0 in 174 (0%) and 1 in 188 (0.5%) in two studies conducted on chronic lymphocytic leukemia/small lymphocytic lymphoma patients who received fludarabine as initial therapy with a long-term followup. 26,27 However, the incidence of therapy-related myeloid neoplasms is significantly higher in the setting of fludarabine combination therapy. [13][14][15][16]26,28 It has been postulated that fludarabine inhibits DNA repair 29 and acts synergistically with DNA-damaging agents, such as cyclophosphomide.…”
Section: Therapy-related Myeloid Neoplasm Post Fcrmentioning
confidence: 99%
“…26,27 However, the incidence of therapy-related myeloid neoplasms is significantly higher in the setting of fludarabine combination therapy. [13][14][15][16]26,28 It has been postulated that fludarabine inhibits DNA repair 29 and acts synergistically with DNA-damaging agents, such as cyclophosphomide. As a result, genetically altered stem cells may escape DNA integrity check and gain survival advantage in the setting of genotoxic therapy.…”
Section: Therapy-related Myeloid Neoplasm Post Fcrmentioning
confidence: 99%
“…1 Exposure to fludarabine may increase the risk of subsequent t-MDS/ AML. [2][3][4][5] Fludarabine is an effective treatment for follicular lymphoma (FL). In combination with mitoxantrone and dexamethasone as frontline therapy, fludarabine induced at least a PR in 96% of patients and a CR in 68%.…”
Section: Introductionmentioning
confidence: 99%
“…A recent analysis performed by Morrison et al 49 revealed another potential adverse effect associated with fludarabine. In patients with CLL, those investigators observed an increased incidence of secondary myelodysplastic syndromes (t-MDS) following treatment with fludarabine (either alone or in combination with chlorambucil).…”
Section: Toxicitymentioning
confidence: 99%